Pengaruh Kepercayaan, Kualitas Produk, Kemudahan Dan Resiko Terhadap Minat Beli Konsumen Secara Online (Studi Kasus Pada Mahasiswa FEB angkatan 2017 yang pernah berbelanja di Shopee) - Nanik Krismonika; Siti Asiyah; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study was conducted at the Faculty of Economics and Business, Islamic University of Malang. The type of study used is a descriptive study with a descriptive analytical approach. The purpose of this study was to determine the impact of reliability and product quality, convenience and risk on consumer buying interest online. The sample used in this study were 100 respondents who were students of the Faculty of Economics and Business class 2017, especially those who had worked in shopee. The data collection method used a questionnaire. The analytical methods used in this study are instrumental testing, normality testing, classical assumption testing,heteroscedasticity test, Multiple linear regression analysis, f-test and t-test using SPPS 16.0 data processing. The results of this study are,trust partially affects consumer buying interest, product quality partially affects consumer purchase interest, convenience partially affects consumer purchase interest, risk partially affects consumer purchase interest. Trust, product quality, convenience, and risk simultaneously affect consumer buying interest online. Keywords: Trust, Product Quality, Convenience, Risk and Consumer Purchase Interest